Perception of quality of life in patients with diabetic foot - Vieira da Silva, João Luiz; Machado Javorski, Eduardo; França Pereira, Raquel; Maria Saalfeld, Rosângela (Journal of the Foot & Ankle, 2025)
Objective: Investigate the factors that influence the perception of quality of life in patients with diabetic feet, with and without ulcers in the lower limbs. Methods: An observational cross-sectional study in 50 adult patients with type 1 and 2 diabetes mellitus, where sociodemographic, clinical, and treatment data were collected, and the Neuropathy Specific Quality Of Life (NEUROQOL) questionnaire was applied, which consists of 35 items that evaluate six domains related to quality of life. Comparisons were performed using appropriate statistical tests, considering the significance of p < 0.05. Results: The mean age was 70 years, with 13 patients having a history of amputations, and 18 had foot ulcers. The domains significantly affected were sensorimotor symptoms, limitations in daily activities, interpersonal problems, and emotional distress. Patients with amputations or ulcers had higher scores, indicating poorer quality of life. Physical activity was associated with significantly better scores in several domains. Conclusion: Patients with diabetic foot complications, such as amputations or ulcers, had a poorer quality of life, especially in the domains related to functionality and emotional well-being. Physical activity proved to be a relevant protective factor. Preventive and therapeutic strategies that promote mobility, health education, and adequate clinical management can contribute to improving the quality of life in individuals with diabetic feet. Level of Evidence IV; Therapeutic studies - investigating the results of treatment; Case series.